Tingkat Kenyamanan Pengunjung terhadap Taman Dipangga berdasarkan Persepsi Pengunjung - Br Manihuruk, Leny Olandia; Ermawati, Mia; Rilansari, Valendya (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2025)
Green open space is very important in realizing a green and sustainable city. This study investigates visitor comfort at Dipangga Park, Bandar Lampung, a green open space with historical tourism potential related to the Mount Krakatau eruption. Despite its significance, the park faces issues such as poorly maintained facilities and poor accessibility, contributing to a declining visitor experience. Using a mixed-methods approach with descriptive statistical analysis and a likert scale. Based on the research results, the comfort level of visitors to Dipangga Park based on visitor perceptions is included in the Uncomfortable category. This shows the level of comfort according to visitors' assessment of conditions that are not good and require improvement and maintenance of the park and facilities to enhance safety, social interaction, and overall visitor satisfaction, contributing to a livable city.